Experimental screening for analgesic and anti-inflammatory effect of novel compounds with a pyrrole heterocycle - Hristina Zlatanova-Tenisheva; Stanislava Vladimirova (Pensoft Publishers, 2024)
The pyrrole heterocycle is found in the chemical structure of numerous drugs with various effects, and it has a reasonably high tolerance and safety profile. The objectives of our study were to assess the analgesic and anti-inflammatory efficacy of six novel compounds with pyrrolic structures. Methods: All trials were carried out on 6-week-old male Wistar rats. Animal pain models using thermal (paw withdrawal, tail-flick) and chemical stimuli (formalin test) were used to examine antinociception. A carrageenan-induced paw edema model was used to assess anti-inflammatory activity. Results: Significant differences between the experimental groups were observed in both early and late phase of the formalin test. Conclusions: The six novel pyrrolic compounds have analgesic action against chemical stimuli in experimental conditions. They do not possess anti-inflammatory activity, or antinociceptive properties against thermal stimuli.